Evaluation of anti-osteoporosis in ovariectomized Wistar rats treated with antler blood by synchrotron radiation X-ray fluorescence microprobe. Issue 1 (2009) - Yang Yang, Jianhong Jianhong; Wang Wang, Ruilin Ruilin; Cao Cao, Yi Yi; Fei Fei, Yurong Yurong; Huang Huang, Yuying Yuying; He He, Wei Wei; Liu Liu, Jing Jing
Abstract : To evaluate the anti-osteoporotic effect of antler blood, the relationship between the change of element content and the bone mineral density (BMD) increase in femur was investigated. Female Wistar rats were randomly divided into three groups: sham-operated group (SHAM, n =5), ovariectomized group (OVX, n =5) and ovariectomized group with antler blood treatment ( n =5). The femoral BMD was analyzed by dual-energy X-ray absorptiometry (DXA) and the element relative content was determined by synchrotron radiation X-ray fluorescence (SRXRF) microprobe. The results showed that the femoral BMD in ovariectomized rats was significantly lower than that of sham-operated rats ( p <0.05) but reversed by antler blood treatment (p<0.05). A further study demonstrated that the relative contents of phosphorus (P), calcium (Ca), zinc (Zn) and strontium (Sr) were obviously lower in ovariectomized rats compared to sham-operated rats but only the relative contents of P, Ca and Zn were normalized by antler blood treatment ( p <0.05). Our experiments revealed that loss of element Ca, P, Zn and Sr was closely related to the BMD reduction in ovariectomized rats and the anti-osteoporotic effect of antler blood was mediated by increasing the contents of P, Ca and Zn.